MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PERSEGI PANJANG DI KELAS III SD NEGERI 028226 BINJAI MELALUI MODEL QUANTUM TEACHING TAHUN PELAJARAN 2016/2017 - Lilis Suharty (MES: Journal of Mathematics Education and Science, 2017)
This study aims to find out how to improve learning outcomes Mathematics students class III SD Negeri 028226 can be increased by using learning model quantum teaching. This study is a classroom action research. The approach used in this study is a qualitative approach to the type of classroom action research. The subject of this research is the third grade students of SD Negeri 028226 Binjai with the number of respondents 25 students. Data from this study were collected through test results and observation results. Based on the results of the action obtained 87.5% who have completed learning. Thus in accordance with the established criteria that the model of quantum teaching can improve student learning outcomes in the Material rectangle students class III academic year 2016/2017